POLITIK MEDIA; SEBUAH PELAJARAN KEBERPIHAKAN MEDIA DALAM PEMILIHAN PRESIDEN TAHUN 2014 - Fiandy Mauliansyah (SOURCE : Jurnal Ilmu Komunikasi, 2018)
When the transitional political climate is now sweeping Indonesia, the media is often an instant reference for public attitudes to certain social phenomena due to the crisis of their direct communication with public officials. The media can also be subjects who manipulate political statements or events because of the pressure of the economic and political interests of their owners or managers. In a transitional political climate, there is media feudalistic behavior in the form of giving more expression space to public figures (extra ordinary people), opinion leaders rather than ordinary people in society. Political leaders are placed as active subjects as producers of information and issues that can always be correlated on a macro and constituent basis as objects that accept the top-down flow of information. Keywords: Politic of Media, Media Oligarchy, Presidential Election